Middle Cerebral Artery Fenestration Accompanying Stroke - Abdul Rahim, Ezamin; Mohd Yaakob, Mohd Naim; Kamis, Mohd Fandi Al-Khafiz; Muda, Ahmad Sobri; Md Noh, Mohamad Syafeeq Faeez (The Interventionalist Journal, 2023)
The article briefly discusses the association of middle cerebral artery fenestration and stroke.